Ethnomedicinal relevance of selected monocot taxa from different geographical regions of Pakistan - Bahadur, Saraj; Ahmad, Mushtaq; Zafar, Muhammad; Begum, Najla; Ali, Maroof; Kumar, Tanweer; Yaseen, Muhammad (Ethnobotany Research and Applications, 2023)
Background: Pakistan has a unique biodiversity of monocotyledon flora and due to its unique climatic condition a huge number of medicinal plants are distributed in the area. Ethnobotany plays a crucial role in understanding the dynamic relationships between biological diversity and social and cultural systems. However, studies about the ethnomedicinal significance of monocot taxa in Pakistan are very limited. Methods: This study documented the indigenous uses of selected medicinal monocot taxa. The ethnomedicinal data was obtained through semi-structured interviews with the local men, women and herbalists of the area. The ethnomedicinal data were analyzed by different quantitative indices i.e. Use value (UV), frequency of citation (FC), relative frequency of citation (RFC), and information consent factor (ICF). Results: In the present study, selected medicinal monocots belonging to seven families were collected from different geographical regions of Pakistan. Family Amaryllidaceae was reported as higher number of used species. Most often used parts were noted as bulbs followed by leaves and roots. The most frequent mode of preparation method was found as a decoction and raw form. Nine different disease categories were reported including respiratory diseases, antidote, gynecological problems, urogenital problems, digestive disorders, glandular disorders, blood circularity system disorders, dermatological problems, and musculoskeletal disorders. Among them, the respiratory disorders show the high value of ICF. Conclusion: The study document showed that selected monocot taxa were used as folk medicine against various diseases. Medicinal monocots having high used value help to identify a phytochemical compound that is bioactive and indispensable for the synthesis of novel drugs for various diseases. Keywords: Monocotyledons taxa, medicinal value, medicinal usage; local communities; ethnobotanical indices.